Evaluation of the Hamaker constants in polymer/water systems based on the Hansen solubility parameters - Hiroyuki Ohshima; Shin-ichi Takeda (Next Materials)
We recently proposed a simple method for calculating the Hamaker constant, which characterizes van der Waals interactions between materials, using the Hansen solubility parameters for non-polar liquids, polar liquids, and polymers. The obtained values of the Hamaker constant agree well with the exact results obtained from the rigorous Lifshitz theory. In this paper, we present a method for evaluating the Hamaker constants in polymer/water systems using the Hansen solubility parameters. We consider the following three cases: (i) the Hamaker constant for a polymer and water across air, (ii) the Hamaker constant for a polymer and air across water, and (iii) the Hamaker constant for two identical polymers across water. Our results show that the commonly used combining relations, which estimate unknown Hamaker constants from known ones, provide good approximations for case (i) but not for cases (ii) and (iii). To improve this, we propose modified combining relations for cases (ii) and (iii). By using the original combining relation for case (i) and the modified versions for cases (ii) and (iii), we derive simple equations for the Hamaker constants expressed in terms of the Hansen solubility parameters. The values calculated using our proposed equations for all three cases show good agreement with the exact values obtained from the rigorous Lifshitz theory.